Does suicidal desire moderate the association between frontal delta power and psychological pain? - Meerwijk, Esther L.; Weiss, Sandra J. (PeerJ, 2016)
Psychological pain frequently underlies thoughts of suicide. We investigated if recent suicidal desire moderated the association between potential neurophysiological markers and psychological pain assessed on the Psychache Scale (PS) and the Orbach & Mikulincer Mental Pain Questionnaire (OMMP). The OMMP specifically assesses current psychological pain that may more readily capture emotions present during recent suicidal desire. In contrast, the PS leaves the timeframe undefined. A secondary analysis was conducted of resting-state EEG data and heart rate obtained in adults with a history of depression. In simultaneous multiple regression models, while controlling for depressive symptoms, recent suicidal desire moderated associations with right-frontal EEG delta power (ΔR2 = .07, p < .01) and low-frequency heart rate variability (nonsignificantly) for pain assessed on the PS. No indication for moderation was found for pain on the OMMP. The relationship between the two measures of psychological pain was stronger for individuals with recent suicidal desire (r = .75, p < .01 vs. r = .50, p < .05). The findings suggest that, unless a respondent’s psychological pain is recent and substantial, the PS may not capture the intensity of current psychological pain as effectively as the OMMP.
Keywords: Psychological pain; Mental pain; Suicide; Heart rate variability; EEG; Psychological measurement